Acid sulfite pretreatment in the enzymatic hydrolysis of Cytisus striatus: optimization strategy - Vaz, Álvaro (2020)
Ethanol production from lignocellulosic material includes three major steps: biomass pretreatment, which fragments the lignocellulosic matrix to facilitate the enzymes access to the substrate; hydrolysis, where the polysaccharides are converted into fermentable sugars (e.g. glucose and xylose); and finally, fermentation that produces ethanol or other biologically based chemicals (e.g. lactic acid, succinic acid). The aim of the present work was to study the effect of some operative variables of the pretreatment stage, namely sodium hydrogen sulfite and sulfuric acid loadings, temperature and time, on the release of sugars in the enzymatic hydrolysis of Cytisus striatus, performed applying a Novozymes® cocktail, with fixed charges and operating conditions. Wood branches were chipped and submitted to different reaction conditions, with a central composite experimental design 2^4+star, exploring the following variables: sulfuric acid charge (0-3%, on wood), sodium bisulfite charge (0-4 %, on wood), maximum temperature (150-190ºC) and time at maximum temperature (0-30 minutes). After pretreatment, the acid hydrolysates were recovered, the solid residues were mechanically disintegrated and thereafter subjected to enzymatic hydrolysis with an enzymatic cocktail from Novozymes®. Sugars and by-products released in the sulphite pretreatment and enzymatic treatment hydrolysates were analyzed by HPLC.